PENGEMBANGAN APLIKASI MATDA (MATEMATIKA BANGUN DATAR) BERBASIS ANDROID PADA MATERI KELILING DAN LUAS BANGUN DATAR - Choiriyah, Ayu Nanda; Isnanto, Isnanto; Marshanawiah, Andi; Aries, Nur Sakinah; Pakaya, Widi Candika (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This research was motivated by the low level of understanding among fifth-grade students at SD Inpres 3 Toili regarding the area and perimeter of flat shapes, due to limited learning media and the low utilization of technology in the learning process. The objective of this study was to develop an Android-based Matda (Flat Shape Mathematics) application that meets the criteria of feasibility, practicality, and effectiveness for the circumference and area of ??flat shapes. The research method used was development research using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The subjects were eight fifth-grade students at SD Inpres 3 Toili, Banggai Regency. In the feasibility test, the Matda application was validated by a team of experts. The summary of validation results from three experts (media experts, material experts, and user experts) yielded a score of 93.7%, categorized as